COMPARISON OF THE CLINICAL COURSE OF OSLT WITH THE NATURE OF DISORDERS OF THE MICROFLORA OF THE UPPER RESPIRATORY TRACT IN CHILDREN - Samieva Sh.U; Olimjanova F.O; Olimjanova Z.O (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
Acute respiratory diseases are the most common in childhood. Together with influenza, they account for at least 70% of all morbidity in children. Acute stenosing laryngotracheitis is one of the most serious manifestations of acute respiratory diseases in young children, requiring hospitalization of the child and intensive care [15].